Commonwealth of Pennsylvania's GED graduates progress. - Gary J. Dean (Adult Education Research Conference, 1997)
A follow-up study of 3,099 GED graduates in Pennsylvania from 1974 through 1994 was conducted to identify changes in employment characteristics, living arrangements, and income, as well as preparation for the GED, further education, and outcomes of passing the GED. All findings indicated that GED graduates perceived obtaining the GED as extremely beneficial.